Studi Tingkat Kepadatan Lalat di Pasar Mardika Kota Ambon - Andriana Ritje Nendissa (MOLUCCAS HEALTH JOURNAL, 2022)
Flies are insects that are vectors of disease in humans. Based on an initial survey at the Mardika Market, Ambon City, there were many piles of garbage and many flies were seen in the piles of garbage. Garbage in the Mardika Market in Ambon City is not transported every day so that it can become a breeding ground for flies, because there are many piles of rotting garbage which are the most potential places to find food and breed. In Mardika Market, there are many flies, especially in vegetable shops, chicken shops, fruit shops and chicken shops. The existence of these flies is due to factors that support life for flies. The presence of flies can be used as an indicator of poor sanitation in a place. The purpose of this study was to determine the level of fly density in the Mardika Market, Ambon City. This research is descriptive in nature by describing the research location in the market to attach the design at the Mardika Market, Ambon City. The results showed that the rate of density at each point of sale had exceeded the standard of 7-22 so it could be said to be dense. The factors that can affect the breeding of flies are; Distance, Temperature and Light. Suggestion ; for the Government and the City Sanitation Service as well as sellers in the market so that they can pay attention to environmental sanitation in the market and the factors that affect the speed of flies.Keywords: Flies Density Level, Distance, Temperature and Light